Léxico e sociedade: Um estudo sociolinguístico sobre os neologismos em blogs de política durante o segundo turno eleitoral de 2014 - Silvana Cristina Romero (2017)
This dissertation based on the sociolinguistic perspective (LABOV, 2008 [1972], 2001, 1990, 1982) of the relationship between lexicon and society to analyze the occurrences of neologisms during the second electoral round of 2014 in Brazil in two political blogs. Based on the hypothesis that the gender and ideological profile of the user in these virtual spaces influence the choice of certain lexical processes (conservative and innovative), our research aimed to observe how these extralinguistic factors are operating in blogs of opposite spectra: Left and Right. In our analysis, we found that in the general context of occurrences, the right-wing blog used more neologisms than the left, during that period, 5,403 and 4,157, respectively. In relation to the general picture about gender, men favored prefixal derivation, syntagmatic composition and portmenteau, while women preferred the processes by loan words and subordinative composition. From the masculine gender equalization, men on the left blog chose prefixal derivation, loan words and syntagmatic composition, and men on the right-wing blog chose portmanteau, semantic, suffixal derivation and subordinative composition. In the comparison between the female gender, women in the left-wing environment favored the prefixal derivation and the syntagmatic composition and the women in the right blog favored the portmanteau and the semantic neologism. In relation to the ideological profile, the general picture shows that left-wing users prefer the processes by prefixal derivation, syntagmatic composition, loan words and acronyms, while the right-wing ones prefer subordinative composition, portmanteau and semantic. Crossing the factors of gender and ideological orientation, the general picture of men shows that those under the left profile they prefer prefixal derivation, while those under of the right profile favor the portmanteau. In the comparison between the female gender under the respective profiles, we observe that the left favored the acronyms and the right preferred the processes by portmenteau and semantic. The results of this synchronic research make it possible to evidence that the preference for certain patterns of formation is influenced by extralinguistic factors, such as gender and ideological profile, highlighting socio-historical aspects in the functioning of neology within the vocabulary on politics and the relevance of the studies that aimed to explain between lexicon and society.